Quantitative Assessment of the Time to End Bainitic Transformation - Miguel A. Santajuana; Adriana Eres-Castellanos; Victor Ruiz-Jimenez; Sebastien Allain; Guillaume Geandier; Francisca G. Caballero; Carlos Garcia-Mateo (Metals, 2019)
Low temperature bainite consists of an intimate mixture of bainitic ferrite and retained austenite, usually obtained by isothermal treatments at temperatures close to the martensite start temperature and below the bainite start temperature. There is widespread belief regarding the extremely long heat treatments necessary to achieve such a microstructure, but still there are no unified and objective criteria to determine the end of the bainitic transformation that allow for meaningful results and its comparison. A very common way to track such a transformation is by means of a high-resolution dilatometer. The relative change in length associated with the bainitic transformation has a very characteristic sigmoidal shape, with low transformation rates at the beginning and at end of the transformation but rapid in between. The determination of the end of transformation is normally subjected to the ability and experience of the “operator” and is therefore subjective. What is more, in the case of very long heat treatments, like those needed for low temperature bainite (from hours to days), differences in the criteria used to determine the end of transformation might lead to differences that might not be assumable from an industrial point of view. This work reviews some of the most common procedures and attempts to establish a general criterion to determine the end of bainitic transformation, based on the differential change in length (transformation rate) derived from a single experiment. The proposed method has been validated by means of the complementary use of hardness measurements, X-ray diffraction and in situ high energy X-ray diffraction.